Millennium Nutrient N,N-Dimethylglycine (DMG) and its Effectiveness in Autism Spectrum Disorders - Dhanjal, Daljeet S.; Bhardwaj, Sonali; Chopra, Chirag; Singh, Reena; Patocka, Jiri; Plucar, Bohumir; Nepovimova, Eugenie; Valis, Martin; Kuca, Kamil (Current Medicinal Chemistry, 2022)
Autism is a neurodevelopmental disorder belonging to the autism spectrum disorder (ASD). In ASDs, the individuals show substantial impairments in social communication, repetitive behaviours, and sensory behaviours deficits in the early stages of their life. Globally, the prevalence of autism is estimated to be less than 1%, especially in high- -income countries. In recent decades, there has been a drastic increase in the incidence of ASD, which has put ASD into the category of epidemics. Presently, two US Food and Drug Administration-approved drugs, aripiprazole and risperidone, are used to treat symptoms of agitation and irritability in autistic children. However, to date, no medication has been found to treat the core symptoms of ASD. The adverse side effects of conventional medicine and limited treatment options have led families of autistic children to turn to complementary and alternative medicine (CAM) treatments, which are perceived as relatively safe compared to conventional medicine. Recently N, N-dimethylglycine (DMG), a dietary supplement, has emerged as a useful supplement to improve the mental and physical state of children with ASD. The current review discusses ASD, the prevalence of ASD, the CAM approach, and the efficacy of CAM treatment in children with ASD. Moreover, it highlights the chemistry, pharmacological effect, and clinical studies of DMG, highlighting its potential for improving the lifestyle of children with ASD.
Keywords: neurological disorders